Westernization of Arab Muslim women in the light of the changes of globalization Iraqi women as a model (field study) (Journal of the College of Basic Education, 2022)
The western globulization hanges in its different Sides led to create unhealthy state In side our Arabic homes and in Iraq in private . It is presented by westernizing the Arabic woman . As aresult of contrabic tion in the ideality valu ation and standard of behaviour . What she gets from local Islamic and Arabic education and international western education which is completely different from her own . Through international establishing organizations .. Clnternets satalites . and from places of social contacts …. Etc … ) The led to the appearance of an adequate and unharmonical behaviour and irritable standard;besides،the social diversion wich didn’t fit the reality of our Islamic societies That made us feel its influence s and effects on woman through her trying hard to imitate the western woman in her most formal behaviour.it doesn’t suit or go with the valuations of social religion and its roots .swch as the increase of the level of divorce cases and the decrease of marriage،woman bet rayal at ،sexual deviation and prostitution (whoredom)etc . The study depends upon both the sight sides and the ground sides،on agroup of methods particularly،the history methoud and finally the reading method. study has reached agroup of results،the important onse are; - There is alink between globulization and the increase of illegal sexual،intercourse among the adults which was assured by(94)social researchers out of 150 . -ther is a relation between globulization and the increase of the way of consumption with women of high.class and that was emphasized by (120)social researchers out of (150).-The west has contribibuted in the spread of a false awareness (conscious)to some girls or females about life ،love، beauty and illegal pleasure، and also through media means. And that came from (103)out of (150).The study emphasized that globalization has affected in an unhealthy way upon womans free-time to the benefit of the educational eye-watch of films and songs on the counterpart of the family and bringing children up to alevel of (87)out of (150).